Relationship between fanaticism and aggression among football spectators in Malaysia / Darwina Mohd Ashari - Mohd Ashari, Darwina (2013)
The purpose this study was to identify the level of fanaticism and aggression among football spectators in Malaysia. It was also done to determine the relationship between fanaticism and aggression among football spectators in Malaysia. 382 respondents (males = 310, females = 72) aged 18 years old and above participated in this study. The methods involved in this study was respondents who watched football match in the stadium by answering a set of questionnaires. Findings in this current study showed a moderate positive relationship between overall fanaticism factors and aggression factors among football spectators in Malaysia (r=0.32, p<0.05). A significant very strong positive relationship between physical and anger (r=0.83, n = 382, p<0.05). Verbal and hostility (r=0.66, n = 382, p<0.05) also showed a strong positive relationship. But the result found negligible relationship between verbal and anger (r=-.16, p<0.05). Therefore, there is a strong positive relationship between the aggression’s factors. There was a weak positive relationship between the two variables of fanaticism, (r=0.27, n = 382, p<0.05) also can be found in this study. It can be concluded that fanaticism may affect the behavior of spectators to be more aggressive. The researcher recommended that generalisations of the findings beyond football game must be inferred with caution and the rights of other spectators should be protected by having security cameras on the venues.